Study of the CKM angle γ sensitivity using flavor untagged decays *Supported by National Natural Science Foundation of China (NSFC) (11925504, 11975015); the 65th batch of China Postdoctoral Fund; the Fundamental Research Funds for the Central Universities, CNRS/IN2P3 (France), and STFC (United Kingdom) national agencies. Part of this work was supported through exchanges between Annecy, Beijing, and Clermont-Ferrand, by the France China Particle Physics Laboratory (i.e. FCPPL). (February 2021) - Ao 敖, D. 冬; Decamp, D.; Qian 钱, W. B. 文斌; Ricciardi, S.; Sazak, H.; T'Jampens, S.; Tisserand, V.; Wang 王, Z. R. 子睿; Yang 杨, Z. W. 振伟; Zhang 张, S. N. 舒楠; Zhou 周, X. K. 晓康
Abstract: A sensitivity study on the measurement of the CKM angle from decays is conducted using the D- meson reconstructed in the quasi flavour-specific modes, , and, as well as CP -eigenstate modes and, where the notation corresponds to a or meson. The LHCb experiment is presented as a use case. A statistical uncertainty of approximately can be achieved with the collision data collected in the LHCb experiment from 2011 to 2018. The sensitivity to should be of the order after accumulating 23 fb -1 of collision data by 2025, whereas it is expected to improve further by 300 fb -1 by the second half of the 2030 decade. The accuracy is dependent on the strong parameters and, which together with describe the interference between the leading amplitudes of the decays.